Методологія системного моделювання показників технічного рівня підшипників кочення - Гутиря, Сергій Семенович; Гайдамака, Анатолій Володимирович (НТУ "ХПІ", 2016)
Запропоновано та практично опрацьовано методологію моделювання показників технічного рівня роликових підшипників у складі букс рейкового транспорту (РПБРТ), що включає системну ієрархічну модель комплексного показника технічного рівня підшипника, обґрунтування номенклатури одиничних і комплексних показників якості РПБРТ та оригінальні методики їх розрахунків, удосконалені методи випробувань модернізованих конструкцій. За результатами моделювання визначено системний показник технічного рівня для базової конструкції РПБРТ, виявлено наявні резерви її вдосконалення за показниками вантажності, внутрішньої динаміки та енергетичної ефективності та забезпечено підвищення системного показника технічного рівня модернізованих конструкцій РПБРТ шляхом запровадження низки інноваційних конструктивних і технологічних рішень.

It is offered and approved methodology of modeling of indicators of a technical level of roller bearings as a part of axle boxes of rail transport (RBABRT), including system hierarchical model of a complex indicator of a technical level of the bearing, justification of the nomenclature of single indicators of quality and original techniques of their calculations, and also advanced test methods of the modernized designs. By results of modeling the system indicator of a technological level for a basic design of RPBRT is defined, is established improvement reserves on indicators of loading capacity, internal dynamics and power efficiency, increase of a system indicator of a technical level of the modernized RPBRT designs by introduction of a number of innovative constructive and technological solutions is provided. On the example of roller cylindrical bearings as a part of axle boxes cargo and sleeping cars efficiency of numerical display of indicators of quality of the main structural and functional office properties of rolling bearings is proved, that allows to consider known and new designs, details and their elements as subsystems of the multiple purpose hierarchical model which is based on the uniform principles, axioms, hypotheses.
Methodology of system simulation performance technical level of rolling bearings
Keywords: роликовий циліндричний підшипник; сепаратор; статика; кінематика; показники якості; модель технічного рівня; cylindrical roller bearing; separator; statics; quality indicators